How do Motivation and Work Environment Affect Bank Employees Performance? - Valentina Kurniawati; Singgih Tiwut Atmojo (Department of Management - Institut Shanti Bhuana, 2021)
The purpose of this study was to determine the influence of work motivation and work environment on the performance of employees of PT Bank Mandiri (Persero), Tbk Branch of Singkawang. This research uses quantitative research Sample of this study were all employees of PT Bank Mandiri (Persero) Tbk, Singkawang branch is 63 people.Based on the analysis that has been carried out, it is concluded that the results of multiple regressions explain the variable X1 is work motivation and X2 is work environment, which has a positive effect on the performance of the variable Y is the performance of the employees . The magnitude of the results of the simultaneous test (F-test) obtained an F value of 53.336 with a significant probability of 0.000, the partial test results (t-test) obtained that the motivation variable has a t-count value of 2.362>t table 1.99897 and a significance value of 0.021 < 0.05. H1 is work motivation has a positive effect on performance. The work environment variable has a t value of 5.926> t table 1.99897 and a significance value of 0.000 <0.05 H2, which means that the work environment is accepted, meaning that individual variables are declared to affect performance.